2014
DOI: 10.2139/ssrn.2436936
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating Weights for Burden Sharing Rules Among Heterogeneous Parties: Empirical Evidence from a Survey Among Delegates in International Climate Negotiations

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
1
7
0
1
Order By: Relevance
“…Many of these distribute their fairness references roughly evenly between Responsibility and Capability, which seem to be the most widely accepted principles in the negotiation. This finding is in line with previous empirical analyses of the topic, most notably Hjerpe et al (2011) and Kesternich et al (2014). The tendency of distributing references to several fairness principles might be interpreted as good news for the prospects of reaching a common conception of fairness.…”
Section: Clashing Fairness Conceptionssupporting
confidence: 91%
See 2 more Smart Citations
“…Many of these distribute their fairness references roughly evenly between Responsibility and Capability, which seem to be the most widely accepted principles in the negotiation. This finding is in line with previous empirical analyses of the topic, most notably Hjerpe et al (2011) and Kesternich et al (2014). The tendency of distributing references to several fairness principles might be interpreted as good news for the prospects of reaching a common conception of fairness.…”
Section: Clashing Fairness Conceptionssupporting
confidence: 91%
“…For these and other reasons, the empirical literature has often suggested that differing fairness conceptions among parties in the climate negotiations constitutes an obstacle to the creation of an ambitious and effective climate agreement (Hjerpe, Löfgren, Linnér & Hennlock, 2011;Kesternich, Löschel & Ziegler, 2014). Therefore, an answer to why such conceptions differ in the first place would be helpful to evaluate the prospects for reaching such an agreement.…”
Section: Why Does Fairness Matter In Climate Negotiations?mentioning
confidence: 99%
See 1 more Smart Citation
“…Other scholars discovered that the dictator's sales quota can be increased effectively through self-introduction, in-depth understanding and other communication practices (Frey & Bohnet, 2014). Kesternich, Löschel, & Ziegler et al (2014) reveal that the burden sharing rules can partially reduce fairness bias in emission reduction negotiation. Lohse, Goeschl, & Diederich, (2017) find the positive correlation between mean response time and contribution of each party.…”
Section: Bargaining Communication and International Climate Negotiationmentioning
confidence: 99%
“…Litteraturen på klimaforhandlinger har foreslått at multilaterale klimaavtaler har høyest potensial for etterlevelse hvis de er basert på en universell forståelse av rettferdig byrdefordeling mellom partene (Ringius, Torvanger & Underdal 2002;Hjerpe et al 2011;Kesternich, Löschel & Ziegler 2014;Young 2014;Tørstad & Saelen 2017). Til tross for at Parisavtalen forsøker nettopp å unngå streng byrdefordeling, åpnet en mer balansert og inkluderende beslutningsprosess enn tidligere muligheten for å definere mål og provisjoner som er mer allment gyldige og aksepterte enn i tidligere avtaler.…”
unclassified